Implications of COVID-19 on teachers’ personal values - Junior, Luiz Gonzaga Lapa; Mourão, Ada Raquel Teixeira; Peruzzo, Marcela Pesci; Alexandrino, Leticia Keroly Bezerra; Leão, Lucineide Melo de Paulo; Ribeiro, Libya Raquel Gomes Vicente; Ferreira, Sonia Maria Escobar de Matos; Monteiro, Maria Eugênia; Araujo, Eliane de Jesus; Sena, Edilene Ferreira de (Seven Editora, 2023)
The Covid-19 pandemic has reverberated throughout the world’s society. In the area of education, in particular, the closure of teaching centers and the abrupt online work has impacted on teachers’ mental health, including changes in values. From this perspective, this study investigated the possible effects of Covid-19 on teachers’ personal values. Values are abstract structures, associated with emotion, influencing choices and behaviors, representing conscious and desired personal goals, and can serve as criteria used by people in their decision-making. Using the quantitative research method through the application of an online questionnaire by Google Forms, the Values Scale validated by Luiz Lapa in 2019 was used as an instrument. The scale is an adaptation of social psychologist Shalom Schwartz’s Refined Value Questionnaire (PVQ-R). Among other results, there are indications of an increase in the values of universalism, benevolence (values of Self-transcendence), safety and conformity (values of Conservation) and a decrease in the importance of the values of stimulation (values of Openness to change) and power (values of Self-promotion). Therefore, in this context, there are indications of changes in teachers’ personal values due to Covid-19. DOI:https://doi.org/10.56238/emerrelcovid19-038